Variation of choroidal thickness with refractive error as measured by optical coherence tomography / Norazwanie Azimi - Azimi, Norazwanie (Faculty of Health Sciences, 2015)
The primary objective of this study was to examine the differences in choroidal thickness with refractive error as measured with optical coherence tomography by conducting a systematic review of the literature which included published research conducted from 2009 to 2014. The first step of the review was developing an answerable question to address the problem. In this review the question was formulated using the PICO framework, which defines population (P), intervention (I), comparison (C) and outcome (O) respectively. The population (P) in this study was adult or children, the intervention (I) was studies that used optical coherence tomography in the measurement while the outcome (O) was choroidal thickness. There was no comparison (C) done in this review as it was not necessary. Previous studies on myopic eyes showed reduced in choroidal thickness. Meanwhile, previous studies performed in the hyperopic anisometropic amblyopic eyes found increment in the choroidal thickness as compared to the fellow eyes and the control eyes. Based on previous researches, there were consistent reports with the correlation between thickness of the choroid and refractive error. In addition, highly myopic eyeballs correlated with choroidal thinning. Studies agreed that thinning of choroid is observed in the more myopic eyes compared to the non-myopic eyes. Studies also supported the association between choroidal thickness changes with refractive error. In conclusion, there was association between choroidal thickness changes with refractive error.